3D Printing of Personalized Medications: Current Trends and Future Prospects - Unuel Gerb; Birty Anggil (Yayasan Adra Karima Hubbi, 2025)
Background: 3D printing technology, also known as additive manufacturing, has rapidly advanced and is now being explored for its potential in creating personalized medications. This innovative approach offers the possibility of producing customized dosage forms tailored to individual patient needs, addressing issues such as precise dosing, polypills, and patient compliance. Objective: The study aims to review the current trends in 3D printing of personalized medications, exploring its applications, technological advancements, regulatory challenges, and potential future directions. The focus is on understanding how this technology can revolutionize pharmaceutical manufacturing and patient care. Methods: A comprehensive literature review was conducted, analyzing academic articles, patents, and regulatory documents published between 2015 and 2023. The study examined various 3D printing techniques, such as fused deposition modeling (FDM), stereolithography (SLA), and selective laser sintering (SLS), and their applications in pharmaceutical production. Data were collected on the types of drugs being printed, the materials used, and the clinical outcomes associated with these personalized medications. Results: The review identified significant progress in the development of 3D-printed medications, with successful cases reported in creating customized dosages and multi-drug polypills. The technology has demonstrated the ability to produce medications with complex release profiles and unique shapes, enhancing patient adherence. However, regulatory hurdles and the need for extensive clinical validation remain major challenges. The study also highlighted emerging trends, such as the use of bioprinting for creating biologically active compounds and the integration of 3D printing with digital health technologies. Conclusion: 3D printing holds promising potential for revolutionizing the pharmaceutical industry by enabling the production of personalized medications. While significant advancements have been made, further research and regulatory developments are necessary to fully realize its benefits. The future of 3D-printed medications will likely involve a combination of technological innovations and new regulatory frameworks to ensure safety, efficacy, and accessibility.